Technology support to a telehealth in the home service: Qualitative observations. (July 2016) - Taylor, Alan; Wade, Victoria; Morris, Greg; Pech, Joanne; Rechter, Stuart; Kidd, Michael; Carati, Colin
Introduction: The Flinders University Telehealth in the Home (FTH) trial was an action research initiative that introduced and evaluated the impact of telehealth services on palliative care patients living in the community, home-based rehabilitation services for the elderly, and services to the elderly in residential aged care. The aim of this study was to understand the issues encountered during the provision of technology services that supported this trial. Methods: A mixed methods approach was undertaken to analyse the roles of information and communication technology (ICT) and clinical staff in design, technology management and training. The data sources were staff observations and documents including job logs, meetings, emails and technology descriptions. Results: Use of consumer technology for telehealth required customisation of applications and services. Clinicians played a key role in definition of applications and the embedding of workflow into applications. Usability of applications was key to their subsequent use. Management of design creep and technology services, coupled with support and training for clinicians were important to maintenance of a telehealth service. Discussion: In the setting described, an iterative approach to the development of telehealth services to the home using consumer technologies was needed. The efficient management of consumer devices in multiple settings will become critical as telehealth services grow in scale. Effective collaboration between clinical and technical stakeholders and further workforce education in telehealth can be key enablers for the transition of face-to-face care to a telehealth mode of delivery.